p53 inhibits CTR1-mediated cisplatin absorption by suppressing SP1 nuclear translocation in osteosarcoma - Yong, Lei; Shi, Yan; Wu, Hai-Long; Dong, Qi-Yuan; Guo, Jing; Hu, Li-Sheng; Wang, Wen-Hao; Guan, Zhi-Ping; Yu, Bin-Sheng (Frontiers in Oncology, 2023)
Osteosarcoma (OS) is a malignant bone tumor mainly affecting children and young adolescents. Multiagent chemotherapy has elevated the 5-year survival of localized OS from 20% to >60%. However, drug resistance severely limits the survival of OS. Cisplatin is a first-line chemotherapy drug for OS, but about 30% of patients do not respond to cisplatin. Nevertheless, cellular factors in cisplatin resistance for OS remain obscure. Copper transporter 1 (CTR1) is the major influx transporter of cisplatin. This study found a negative regulatory relationship between p53 and CTR1. Under cisplatin treatment, p53 knock-out promoted CTR1 expression and cisplatin uptake, while p53 overexpression inhibited CTR1 expression and cisplatin uptake. Further mechanism research showed that p53 regulated CTR1 level not by binding to CTR1 promoter directly but by suppressing the nuclear translocation of transcription factor specificity protein 1 (SP1). We verified that SP1 is directly bound with CTR1 promoter. SP1 overexpression stimulated CTR1 expression, and SP1 knock-down attenuated CTR1 expression. Together, our findings identify the p53-SP1-CTR1 axis as a target for cisplatin resistance and provide evidence for a new oncogenic role of p53 in OS.